THE USE OF GOOGLE PATENTS AS AN INDICATOR OF INNOVATIONS IN THE BRAZILIAN AGRIBUSINESS: AN APPROACH WITH LEXICOMETRIC ANALYSIS VIA IRAMUTEQ (REMUNOM, 2026)
The study investigated innovation in Brazilian agribusiness using patents as an indicator, accessed via Google Patents and analyzed with the lexicometric tool IRAMUTEQ. A total of 584 patent records were collected using sector-related keywords. The analysis revealed three main technological axes. The first is agricultural biotechnology, focusing on the development of genetically modified plants. The second, automation and agricultural machinery, emphasizes smart equipment and the use of sensors. The third groups sustainable solutions, such as organic fertilizers and irrigation techniques. The similarity and word cloud analyses highlighted connections between terms such as "sustainability," "efficiency," "automation," "biotechnology," and "productivity." This indicates that the innovations primarily aim to address challenges related to efficient resource use. The results provide valuable insights for strategic direction, such as fostering collaboration between the government and companies. This partnership can leverage information on potential sector bottlenecks or gaps to channel investments into innovation and development programs in the most promising areas, thereby fostering public-private partnerships. The adopted methodology—integrating patent data with lexicometric analysis—proves to be a robust tool for monitoring technological trends and supporting the sustainable development of Brazilian agribusiness.